Intermediate harvesting intensities enhance native tree performance of contrasting species while conserving herbivore diversity in a Patagonian woodland - Nacif, Marcos Ezequiel; Quintero, Carolina; Garibaldi, Lucas Alejandro (Forest Ecology and Management)
Sustainable forest management should optimise the balance between tree productivity and biodiversity conservation. One strategy to achieve both is the use of native plantations in biomass extraction systems. However, it is unknown how different native tree species and their herbivores respond to a gradient of biomass extraction. In a Patagonian woodland, we planted six native tree species of high wood value and contrasting physiological traits, in plots with increasing harvesting intensities (HI: 0, 30, 50 or 70% of basal area removal), and measured herbivory rates, herbivore guild diversity, and sapling survival and growth. To understand whether herbivore diversity in non-planted wild species was affected by harvesting intensity, we performed the same herbivore measures in six wild woodland plant species. Herbivory rates and herbivore guild diversity showed similar responses to HI, being highest on saplings growing at 30% (N. dombeyi, N. antarctica, N. pumilio and N. alpina) or 30% and 50% (N. obliqua) HI. Deciduous tree species were consumed at a higher rate and held more diverse guilds, whereas evergreen species were consumed at a lower rate or barely damaged. Differences among species seem to be mostly driven by leaf habit and nitrogen content. In turn, higher HI increased the heterogeneity of arthropod guild composition, being N. alpina and N. pumilio the species with most variation in guild composition across HI. Contrariwise, regarding the non-planted wild woodland species, there was no effect of HI on herbivory rates or guild diversity. Finally, planted tree species survived and grew more at 30% and 50% HI despite supporting higher leaf damage, except for N. antarctica which showed a similar survival rate across all HI. Species with highest performance were A. chilensis and N. obliqua; but differences regarding plant performance among species were not explained by their physiological traits. Approximately one-third to mid harvesting intensities in this Patagonian woodland were optimal for enhancing ...